Influence of microstructure and stress on short intergranular stress corrosion crack growth in austenitic stainless steel type 304 - Rahimi, S; Marrow, T (2008)
Intergranular stress corrosion cracking (IGSCC) causes failures in austenitic stainless steels when the appropriate electrochemical, metallurgical and mechanical conditions exist. In this study, the effects of time, applied stress, residual stress and microstructure on population of short crack nuclei has been investigated in sensitised type 304 austenitic stainless steel, tested under static load in an acidified potassium tetrathionate (K2S4O6) environment. Statistical analysis, using the Gumbel distribution method, enables analysis of the growth rate of short crack nuclei. This methodology is being developed, in order to quantitatively evaluate the influence of grain boundary engineering and surface finishing on crack nucleation.